Revisión y optimización metodológica para extraer clorofila-a fitoplanctónica en ambientes acuáticos - Bursztyn Fuentes, Amalia Lara (2022)
The quantification of phytoplankton chlorophyll-a concentration (Chl-a) is a routine determination in limnological, ecological and environmental studies. The aim of this study was to experimentally compare the most frequently used methodologies to determine Chl-a in order to find the most efficient and affordable method for aquatic environments. In three urban water bodies of Ushuaia (Tierra del Fuego, Argentina), we compared 11 methods, in 2 independent essays, which included different sample storage strategies, different solvents, filter cut-off and centrifugation. We observed that the ability to show significant differences in the technique depended on the water body under study. In all cases where significant differences were detected between treatments, hot ethanol (60-70 °C) was the solvent that allowed the best Chl-a extraction. Although the most commonly used method according to our literature survey is the one involving extraction with 90% acetone, the most efficient treatments in our experiment turned out to be those with hot ethanol (with an extraction efficiency between 14 and 98% higher, depending on the treatment and the water body).